Narrativas que se construyen acerca de las publicaciones en las redes sociales en parejas de 19 a 25 años de las Facultades de la Universidad Antonio Nariño (2021)
The present research seeks to analyze the narratives that are built about the publications on social networks of the couples of the Antonio Nariño University, in an age range that oscillates between 19 and 25 years. The research was carried out from a qualitative perspective, as a methodology an interview with open questions was used, giving way to the narratives of the participants, different positions are obtained regarding the appreciation they give to social networks and the ways in which it intervenes in the dynamics as a couple.